Batasan Kriteria Open Legal Policy dalam Pengujian Konstitusionalitas Presidential Threshold - Hariyanto, Ruth Crista Vanesa; Kusumawati, Erna Dyah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2024)
The Presidential Threshold policy in Article 222 of Law Number 7/2017 on General Elections has always been debated, even since it was first enacted in Article 5 paragraph (4) of Law Number 23/2003 on General Elections of the President and Vice President. The Indonesian Constitutional Court (MKRI), as the highest judicial institution entrusted to preserve the spirit of the constitution, is certainly a place to log a complain about the debate that was triggered by the existence of this norm. Although the MKRI's judgement on the constitutionality of the Presidential Threshold policy is final and binding in nature, it is still considered incomplete. This incompleteness occurs due to lack of consideration on the substantive issue and only answered it as an Open Legal Policy. In fact, according to its function, MKRI should also examine the norms of a law based on the spirit of the constitution more specifically, which is  up to the principles and fundamentals of constitutionality as the highest norm that has been guaranteed in the constitution. The research method used in this paper is normative juridical. This research aims to find out that the Principle of the Rule of Law, the Principle of Democracy and the Presidential Principle are three important fundamental values that should be used as limitations for MKRI in stating Open Legal Policy in the Presidential Threshold judicial review. By understanding and precisely interpreting the meaning of the Constitution regarding the norms of the Principle of the Rule of Law, the Principles of Democracy and the Presidential Principle, the Presidential Threshold policy should be inconstitutional and MKRI has the authority to cancel the policy. Key Words: Presidential Threshold, Open Legal Policy, Election.